Synthesis, characterization, DNA binding/cleavage, cytotoxic, apoptotic, and antibacterial activities of V(IV), Mo(VI), and Ru(II) complexes containing a bioactive ONS‐donor chelating agent. (15th November 2020) - El‐Afify, Marwa E.; Elsayed, Shadia A.; Shalaby, Thanaa I.; Toson, Elshahat A.; El‐Hendawy, Ahmed M.
Abstract : New V(IV), Mo(VI), and Ru(II) complexes containing the ligand 2, 4‐dihydroxyacetophenone‐ S ‐methyl dithiocarbazate (H2 dhasm); [VO(dhasm)(bpy)] (1 ) (bpy = 2, 2′‐bipyridine), [VO(dhasm)(phen)] (2 ) (phen = 1, 10‐phenanthroline), [MoO2 (dhasm)(imz)] (3 ) (imz = imidazole), [MoO2 (dhasm)(DMSO)] (4 ) (DMSO = dimethylsulfoxide), and [Ru(CO)(PPh3 )2 (dhasm)] (5 ) have been synthesized. The ligand and its complexes were structurally characterized by elemental analyses, IR, 1 H NMR, EPR, ultraviolet (UV)–visible spectroscopies, magnetic susceptibility, and cyclic voltammetry measurements. Single crystal X‐ray crystallography was used to establish the structure detail of (3 ) and (4 ) complexes confirming that the ligand coordinate to the metal ion in a bi‐negative tridentate fashion (dhasm 2−, ONS‐donor) in a distorted octahedral geometry. The interaction with calf thymus DNA (CT DNA) of all compounds was studied by UV–visible and fluorescence spectroscopies. Both studies confirmed that these compounds bind to CT DNA through intercalation mode. The DNA cleavage activity of the complexes was also studied on plasmid DNA using gel agarose electrophoresis, and the results revealed that only complexes (2 ) and (5 ) have superior cleavage activity in the presence of H2 O2 . The cytotoxic activity (in vitro) of the complexes on three human cancer cell lines; human liver hepatocellular carcinoma (HepG2), breast adenocarcinoma (MCF7), and epitheliod carcinoma (Hela); and a normal human lung fibroblast (WI‐38) was studied using MTT assay. The complexes exhibited a strong cytotoxicity effect compared with their parent ligand. The ruthenium(II) complex (5 ) showed the most potent growth inhibition of cancer cells. Also, the mechanism of the apoptotic death in HepG2 cells was studied by observing an increased gene expression of caspase‐3, BAX, P53 and decreased Bcl2 gene expression. The complexes were also screened for their antibacterial activity against gram‐positive and gram‐negative bacteria and showed significant activity against both microorganisms. Abstract : Oxovanadium(IV), dioxomolybdenum(VI), and ruthenium(II) complexes of ONS‐donor ligand have been synthesized and spectroscopically characterized. The binding affinity with CT DNA has been studied using absorption and fluorescence spectra and cleavage activity by gel electrophoresis. Anticancer, apoptotic, and antibacterial activities (in vitro) have been evaluated.